2023
DOI: 10.3390/w15162888
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Geological, Geochemical Modelling and Hydrodynamic Condition for Understanding the Geometry and Flow Pattern of the Aquifer System, Southern Nyírség–Hajdúság, Hungary

Yetzabbel G. Flores,
Mohamed Hamdy Eid,
Péter Szűcs
et al.

Abstract: Geological heterogeneity impacts groundwater flow patterns, necessitating a detailed hydrogeological framework for conceptualization process of aquifer systems. This research developed a new conceptual model of detailed geologic geometry by integrating 133 well-logs, 366 hydrodynamic data and 118 water samples. As new results, systematic 3D log correlation detected four distinct hydrostratigraphic units in the Southern Nyírség–Hajdúság Groundwater Body (East Hungary). The primary aquifer was identified as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…The calculated CAI-1 and CAI-2 show that the majority of groundwater samples exhibit positive values (Fig. 4e), which may highlight the impact of cation exchange between bivalent cations (Ca 2+ and Mg 2+ ) in the host rock and monovalent cations (Na + and K + ) in the groundwater (Al-Mashreki et al, 2023;Eid et al, 2024bEid et al, , 2024aFlores et al, 2023;Wu et al, 2015)…”
Section: Ion Exchange Processesmentioning
confidence: 94%
See 1 more Smart Citation
“…The calculated CAI-1 and CAI-2 show that the majority of groundwater samples exhibit positive values (Fig. 4e), which may highlight the impact of cation exchange between bivalent cations (Ca 2+ and Mg 2+ ) in the host rock and monovalent cations (Na + and K + ) in the groundwater (Al-Mashreki et al, 2023;Eid et al, 2024bEid et al, , 2024aFlores et al, 2023;Wu et al, 2015)…”
Section: Ion Exchange Processesmentioning
confidence: 94%
“…The characteristics of irrigation water are critical in determining the structural and functional attributes of soil, affecting aspects like its ability to allow water flow, its filtration efficiency, and the movement of air within its matrix, all due to the water's specific chemical makeup (Ghodbane et al, 2022;Flores et al, 2023;Eid et al, 2023;(Gad et al, 2023b;Gad and El Osta, 2020;Eid et al, 2022;Gad and El Osta, 2020;Ibrahim et al, 2023). The levels of sodium ions present hold particular importance, as high concentrations can alter soil's natural filtration process by causing calcium and magnesium ions to be replaced via absorption.…”
Section: Effects On Soil Structurementioning
confidence: 99%
“…The region’s climate can be characterized as predominantly continental, with annual mean temperatures ranging from 10° to 11 °C. The annual precipitation varies from 550 to 600 mm, and potential evapotranspiration ranges between 600 and 700 mm/year 44 .
Figure 1 Geographic map created with ArcGIS Desktop v. 10.8 45 , showing the location of the study area within the Eastern part of Hungary.
…”
Section: Study Areamentioning
confidence: 99%
“…Recently, Flores et al 44 conducted an extensive regional-level hydrostratigraphical investigation, concentrating on the upper section of the Nagyalföld aquifer. Their findings revealed that the key hydrostratigraphic components in their study encompass the Pre-Quaternary and Quaternary sequences (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…Statistical analysis and imitative approaches, such as Piper diagrams, Gibbs diagrams, Chadha diagrams, and the ionic ratio are powerful and useful tools for evaluating the chemical characteristics of groundwater and the underlying factors [19][20][21][22]. Geochemical models are valuable in computing chemical reactions occurring in groundwater systems; comprehensive processes like solid dissolution and precipitation; ion exchange; and sorption by clay minerals [23][24][25][26][27][28]. Statistical correlation analysis, which establishes connections between various physicochemical factors, holds promise for advancing groundwater quality management.…”
Section: Introductionmentioning
confidence: 99%